Stigma Sosial Pengangguran di Media Daring Amerika Serikat pada Masa Pandemi COVID-19 - Mercedes Amanda; Evanytha Evanytha; Rustono Farady Marta; Hana Panggabean (Jurnal Komunikasi, 2022)
The social stigma of unemployment during the COVID-19 pandemic related to problems of marginalization. This study explores the construction of the meaning of the social stigma of unemployment in United States online media. This study is a comparative study to compare the construction of the meaning of social stigma between online media usa.today and nbcwashington.com with Entman's framing analysis. The problem formulated through framing is that social stigma makes it difficult for unemployed people to get a job, and stigma creates feelings of inferiority. The cause of the social stigma is the perception of low personal qualities and stigma consciousness. Framing moral judgment is a negative perception in employers' minds and the feeling of shame due to unemployment. Countermeasure suggestion is a wide distribution of vaccines and suggestions about ways to find work. Online media can contribute as agents of change through news framing to improve public perceptions and provide informational support.